Rethinking risk prediction: The role of albumin and other parameters in implant-associated complications after hip or knee arthroplasty. - Petr Domecky; Anna Rejman Patkova; Lenka Zaloudkova; Tomas Kucera; Pavel Sponer; Josef Maly (PLoS ONE)
Background Total hip (THA) or knee (TKA) arthroplasty is still a traumatic and challenging operation that induces inflammation, with a particularly high risk of acute-phase reaction. The aim of this study was to predict the likelihood of implant-associated complications during the preoperative and postoperative course. Methods The prospective observational, non-interventional study of patients diagnosed with primary knee or hip osteoarthrosis undergoing THA or TKA during the study period was conducted. The inflammatory and malnutrition parameters were collected for each patient one day before surgery, two days after surgery, and in outpatient follow-up. Results Of 159 patients analysed, 12 developed implant-associated complications. The albumin, prealbumin, Intensive Care Infection Score (ICIS), Nutritional Risk Index, and white blood cell counts were found to be potential predictors. Notably, preoperative albumin levels significantly differed between groups with and without complications (P-value = 0.042). Conclusion Our study definitively shows that WBC, prealbumin, Nutritional Risk Index, ICIS as a novel marker, and significantly albumin, outperform C-reactive protein in predicting implant-associated complications in hip and knee arthroplasty.